2018
DOI: 10.1128/jcm.01481-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Copan ESwab Transport System for Viability of Pathogenic Fungi by Use of a Modification of Clinical and Laboratory Standards Institute Document M40-A2

Abstract: The Copan ESwab system was evaluated for its ability to maintain the viability of pathogenic fungi. Tests followed the Clinical and Laboratory Standards Institute (CLSI) document M40-A2 roll-plate method at room and refrigerator temperatures. A system was devised for standardizing homogeneous inoculum suspensions of variously sized conidia and sporangiospores of filamentous fungi. A total of 19 clinical and reference strains were standardized to a 0.5 McFarland turbidity standard with a simple photometer. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Aside from bacteria, the ESwab also supports the growth of fungi. 6 Because this is a novel use of the ESwab, the clinical laboratory may offer some resistance, as they do when asked to process a blood culture bottle for a vitrectomy specimen. Furthermore, although becoming more popular, not all laboratories may be familiar with receiving specimens collected in ESwabs.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from bacteria, the ESwab also supports the growth of fungi. 6 Because this is a novel use of the ESwab, the clinical laboratory may offer some resistance, as they do when asked to process a blood culture bottle for a vitrectomy specimen. Furthermore, although becoming more popular, not all laboratories may be familiar with receiving specimens collected in ESwabs.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli and Enterococcus faecalis exhibited resistance to repeated cycles of freezing (–80°C) and thawing in Copan-ESwab tubes, and fewer freeze-thaw cycles yielded better preservation of bacterial viability ( Saliba et al., 2020 ). Copan-ESwab could also effectively maintain the viability of filamentous fungi for at least 48 h ( Gandhi et al., 2018 ). In the present study, Copan-ESwab tubes preserved Candida , the main pathogen causing urogenital tract inflammation in women.…”
Section: Discussionmentioning
confidence: 99%
“…including the yeast C. auris , which is of particular interest to clinicians due to misdiagnosis, link to nosocomial infections and drug resistance of this pathogen. While the recent study by Scansen et al [ 16 ] and Gandhi et al [ 17 ] demonstrated recovery of several Candida spp. and other pathogenic fungi using other commercial STS based on the M40-A2 protocol, they did not investigate recovery of C. auris .…”
Section: Discussionmentioning
confidence: 99%